2011
DOI: 10.1038/mt.2011.107
|View full text |Cite
|
Sign up to set email alerts
|

Stable Human FIX Expression After 0.9G Intrauterine Gene Transfer of Self-complementary Adeno-associated Viral Vector 5 and 8 in Macaques

Abstract: Intrauterine gene transfer (IUGT) offers ontological advantages including immune naiveté mediating tolerance to the vector and transgenic products, and effecting a cure before development of irreversible pathology. Despite proof-of-principle in rodent models, expression efficacy with a therapeutic transgene has yet to be demonstrated in a preclinical nonhuman primate (NHP) model. We aimed to determine the efficacy of human Factor IX (hFIX) expression after adeno-associated-viral (AAV)-mediated IUGT in NHP. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 48 publications
3
98
0
Order By: Relevance
“…There is also an ongoing concern about the potential for episomal loss due to hepatocellular proliferation. Both of these mechanisms have been suggested to account for the observed decline of FIX plasma levels over time after AAV gene therapy in utero or perinatally in both sheep and NHPs [48,49]. Integration of the vector genome into the recipient’s DNA-utilizing vectors such as lentivirus, which allows for transgene replication during cell division, may provide for sustained transgene expression during normal growth and development.…”
Section: Translation For Pediatric Patientsmentioning
confidence: 99%
“…There is also an ongoing concern about the potential for episomal loss due to hepatocellular proliferation. Both of these mechanisms have been suggested to account for the observed decline of FIX plasma levels over time after AAV gene therapy in utero or perinatally in both sheep and NHPs [48,49]. Integration of the vector genome into the recipient’s DNA-utilizing vectors such as lentivirus, which allows for transgene replication during cell division, may provide for sustained transgene expression during normal growth and development.…”
Section: Translation For Pediatric Patientsmentioning
confidence: 99%
“…First, vector potency and toxicity can be determined. Similar studies have been carried out with factor IX gene delivery [84–89]. Second, transgene expression, i.e., factor VIII levels produced by the vector can be measured.…”
Section: Non Genetic Model For Hemophilia Researchmentioning
confidence: 94%
“…87,91 In the liver, scAAV vector result in a 10-to 20-fold higher level of transgene expression compared with a similar dose of a classical AAV vector. 87 In 2011, Mattar et al 80 reported the first unequivocal evidence of a successful gene therapy trial for hemophilia B using a self-complementary rAAV serotype 8 vector carrying the coagulation factor IX coding sequence driven by a liver-specific promoter. The liver produced factor IX, which was secreted to the blood at levels sufficient to improve the bleeding phenotype.…”
Section: Recombinant Adeno-associated Viral Vectorsmentioning
confidence: 98%
“…[76][77][78][79][80]99 Random integration of vector sequences has been demonstrated in established cell lines 100 but only in some cases and at low frequency in primary cultures and in vivo. 78,101,102 In mouse liver, integration of rAAV vector has been quantified at a frequency of less than 2%.…”
Section: Insertional Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation